2004
DOI: 10.1021/jo049671w
|View full text |Cite
|
Sign up to set email alerts
|

A New Fullerene Complexation Ligand:  N-Pyridylfulleropyrrolidine

Abstract: The subject of this paper is a new fullerene building block design with the potential for defined geometry and good electronic communication. The synthesis and characterization of a new pyridinofullerene ligand capable of forming axially symmetric complexes with metalloporphyrins is reported. X-ray structural and molecular modeling studies, (1)H NMR, UV-vis spectroscopy, electrochemistry studies, and fluorescence quenching data support the formation of a strong complex between the new ligand and the metal cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 36 publications
6
44
0
1
Order By: Relevance
“…Our results also suggest a lack of electronic communication between the pyridyl nitrogen atom and te fullerene cage in N-(4-pyridyl)pyrrolidinofullerene [16] as this compound has almost the same reduction potentials as N-methylpyrrolidinofullerene and our derivative 12, which possesses two 4-pyridyl groups. However, such an electronic communication has been claimed to explain a higher binding constant for complex formation between N-(4-pyridyl)pyrrolidinofullerene and ZnTPP (K a = 7.7 × 10 -4 ) in comparison with the similar complex of 3-methyl-2-(4-pyridyl)pyrrolidinofullerene (K a = 1.4 × 10 -4 ).…”
Section: Electrochemical Properties Of the Synthesized Pyridylappendementioning
confidence: 59%
See 1 more Smart Citation
“…Our results also suggest a lack of electronic communication between the pyridyl nitrogen atom and te fullerene cage in N-(4-pyridyl)pyrrolidinofullerene [16] as this compound has almost the same reduction potentials as N-methylpyrrolidinofullerene and our derivative 12, which possesses two 4-pyridyl groups. However, such an electronic communication has been claimed to explain a higher binding constant for complex formation between N-(4-pyridyl)pyrrolidinofullerene and ZnTPP (K a = 7.7 × 10 -4 ) in comparison with the similar complex of 3-methyl-2-(4-pyridyl)pyrrolidinofullerene (K a = 1.4 × 10 -4 ).…”
Section: Electrochemical Properties Of the Synthesized Pyridylappendementioning
confidence: 59%
“…However, such an electronic communication has been claimed to explain a higher binding constant for complex formation between N-(4-pyridyl)pyrrolidinofullerene and ZnTPP (K a = 7.7 × 10 -4 ) in comparison with the similar complex of 3-methyl-2-(4-pyridyl)pyrrolidinofullerene (K a = 1.4 × 10 -4 ). [16] Generally, the electron-withdrawing effect of the fullerene cage on the nitrogen atoms in the addends results in decreased basic properties and lower association constants with ZnTPP, [17] which is inconsistent with the expectation of the authors of ref. [16] …”
Section: Electrochemical Properties Of the Synthesized Pyridylappendementioning
confidence: 88%
“…[13] Electrochemical studies further confirmed this effective coupling between the pyridyl nitrogen atom and the fullerene core based on the fact that the first reduction of the C 60 core was shifted by 40 mV upon complexation with a Zn-porphyrin derivative. [14] Thus C 60 hexakis-adducts 2 and 3 with terpyridyl or pyridyl groups in the trans-1 positions and the corresponding trans-1 bis-adducts 4 and 5 (Scheme 3) were selected as the synthetic targets in the present work. Regioselective formation of trans-1 bis-adducts of C 60 has been a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…After conversion of those potentials versus Ag/Ag + to those versus Fc/Fc + , [33] the values are À1.01 and À1.29 V. The first and second reductions are shifted anodically by 50 and 150 mV, respectively, relative to those of 1 in solution. [14] All peak potentials are proportional to the sweep rate, which was varied between 0.1 and 1 V s À1 , indicating surface-confined behavior due to the immobilization of the electroactive fullerene derivative on the gold surfaces.…”
mentioning
confidence: 99%
“…Precursor 7 was obtained via synthetic routes according to the literature (59). Porphyrin 2 and fullerene 3 were prepared as described previously (60).…”
mentioning
confidence: 99%